Navigating HRM Challenges in Port and Shipping Management: Insights from Maritime Institute Graduates - Retno Sawitri Wulandari (Dinasti Publisher, 2024)
This research delves into Human Resource Management (HRM) strategies within the Port and Shipping Management sector, focusing on the perspectives of graduates from the Maritime Institute (Sekolah Tinggi Ilmu Pelayaran Jakarta). Through qualitative analysis, the study identifies key HRM indicators, including training and development, safety and compliance, talent acquisition and retention, performance management, and leadership development. Additionally, it examines the alignment of HRM practices with international standards, emphasizing the importance of integrating global education benchmarks into organizational strategies. The findings underscore the critical role of HRM in driving professional development and organizational effectiveness within maritime environments. By aligning HRM practices with international standards, organizations can enhance professionalism, promote diversity and inclusion, and foster ethical leadership. This research offers valuable insights for HRM practitioners, policymakers, educators, and industry stakeholders seeking to navigate the complexities of the global Port and Shipping Management sector.